The importance of socializing Indonesian financial accounting standards for SMEs (small and medium, enterprise) in increasing accounting understanding and its implementation - Hamdani; Chanifah, Siti; Anwar, Yuli (Technium Social Sciences Journal, 2020)
The research aims to examine the effect of socialization on accounting understanding and its implementation. This research was conducted at SMEs in the province of Banten with 66 research samples. The research variables consisted of exogenous variables is Indonesian Financial Accounting Standard for SMEs (IFAS SMEs socialization) and intervening variables is accounting understanding, and endogenous variables are the implementation of IFAS SMEs. Data was collected through field surveys using questionnaires and direct interviews to obtain complete information. Support theoretical argumentation, a literature study was conducted. Furthermore, structural model testing (inner models) and hypothesis testing. The results showed that the socialization of IFAS SMEs had a positive and significant effect on the implementation. The socialization of IFAS SMEs has a positive and significant effect on the understanding of accounting and has implications for the implementation of IFAS SMEs for SMEs. The IFAS SMES socialization needs to be carried out by the Cooperative and SMEs Office and professional institutions, such as Institute of Indonesian Chartered Accountant (IAI), to provide understanding to the SMEs, so that they can implement it in business practices. The SMEs must participate in the socialization activities, so that understanding of accounting increases and can implement it.